Youngia baoxingensis, a new species of Asteraceae (tribe Cichorieae) from Sichuan, China - Chen, You-Sheng (Phytotaxa, 2018)
Youngia baoxingensis (Asteraceae, Cichorieae), a new species from Baoxing in Sichuan, China, is described and illustrated. This species belongs to Youngia sect. Mesomeris and is similar to Y. yilingii, but is distinct by its oblong and subentire leaf blade, brown pappus, and 6–7 florets.